2019
DOI: 10.3390/coatings9100643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Properties of the Hybrid and Bilayer MWCNTs—Hydroxyapatite Coatings on Ti Alloy

Abstract: Carbon nanotubes are proposed for reinforcement of the hydroxyapatite coatings to improve their adhesion, resistance to mechanical loads, biocompatibility, bioactivity, corrosion resistance, and antibacterial protection. So far, research has shown that all these properties are highly susceptible to the composition and microstructure of coatings. The present research is aimed at studies of multi-wall carbon nanotubes in three different combinations: multi-wall carbon nanotubes layer, bilayer coating composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…The critical determinant of any coating is its adhesion to the substrate. Such measurements have been already performed for this type of coatings and published in [ 46 ], demonstrating this property suitable for coatings on titanium implants. The average thickness of MWCNTs coating was 7.88 μm ± standard deviation of 0.35 μm.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The critical determinant of any coating is its adhesion to the substrate. Such measurements have been already performed for this type of coatings and published in [ 46 ], demonstrating this property suitable for coatings on titanium implants. The average thickness of MWCNTs coating was 7.88 μm ± standard deviation of 0.35 μm.…”
Section: Resultsmentioning
confidence: 86%
“…Before preparing the suspension, the carbon nanotubes were functionalized using a method described elsewhere [46]. The chemical modification allowed for the introduction of carboxyl groups on the surface of the nanotubes.…”
Section: Preparation Of Suspension Of Functionalized Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research was described by Bartmanski et al for nanoAg [135,136] and nanoCu [137]. The coating composed of nanoHAp, MWCNTs, nanoAg, and nanoCu were developed to obtain antibacterial efficiency, high adhesion, and mechanical strength of coatings [138] also with additions of nanoAg and nanoCu. The ultra-fine Pd-Ag-HAp nanoparticles electrodeposited on protruded TiO 2 layer [139] were considered as plausible for dental implants as increasing their biocompatibility.…”
Section: Metal-ceramics Coatingsmentioning
confidence: 69%
“…Majkowska et al [28] investigated deposition by the electrophoretic method of ceramicceramic coatings composed of hydroxyapatite and carbon nanotubes achieved as bilayers (subsequent deposition) and hybrid coatings (simultaneous deposition). It was shown that the pure multi-wall carbon nanotubes (CNTs) layer showed the best mechanical and biological properties.…”
mentioning
confidence: 99%